A retrospective view of English language learning materials produced in Slovenia from 1945 to the present - Skela, Janez (ELOPE (Ljubljana), 2013)
Taking a historical perspective, this article documents the development of domestically produced English Language Learning (ELL) materials in the period between 1945 and 2013. To this end, reference is made to milestones that marked shifts in linguistic and foreign language teaching paradigms, including aspects of Method and the underlying conception of language. The analysis will draw on aspects of Method in relation to language policy documents (i.e. curricula) and the course books in which these principles are embodied. Through the analysis of these factors we trace the evolution from Grammar-Translation methodology to Communicative Language Teaching in locally produced textbooks which are representative of various historical periods.
Keywords: dokumenti jezikovne politike; domači učbeniki; gradiva za učenje angleščine; metode poučevanja jezikov; zgodovinska perspektiva; zgodovinski pregledi